(untitled) (International Journal of Irrigation and Water Management, 2014)
A field experiments were conducted for two consecutive seasons (2006/2007 and 2007/2008) in Demonstrated Farm, Sudan University of Science and Technology, to study the effect of irrigation intervals at different growth stages on growth, yield component and fiber characteristics of cotton (Gossypium barbadence L.). The experiment was lied out in a complete plots design with four replications. The treatments were standard irrigation every two weeks (W1), extended irrigation intervals of one month during predetermined stages of cotton (W2), the stages were early vegetative growth (W3), early flowering (W4), and early boll ripening (W5). The results revealed that plant height, seed index and lint index were not affected by irrigation intervals. Plant height had significant difference in first season only. Seed yield had significant differences in second picking of both seasons, and first picking of second season. Lint yield showed significant differences in all three picking of first season and first picking of second season. In general irrigation interval every 15 days throughout growth (W1) had the greatest values. On the other hand W4 (30 days interval at early flowering) and W 5 (30 days interval at early boll ripening) showed the lowest values. Meanwhile, fiber characteristics had no clear evidence due to irrigation intervals.